Reefer madness [videorecording (DVD)] - Gasnier, Louis J., 1875-1963; Royale, Pat; O'Brien, Dave, 1912-1969; Short, Dorothy, 1915-1963 (Alpha video classics., 2003)
An exploration of the evils of marijuana. High school kids get hooked on marijuana, which leads to wild behavior, accidents and finally to death and murder.